2021
DOI: 10.1139/gen-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic classification of the bacterial endosymbiont Wolbachia based on next-generation sequencing: is there molecular evidence for its presence in tardigrades?

Abstract: We used high-throughput sequencing of 16S rRNA to test whether tardigrade species are infected with Wolbachia parasites. We applied SILVA and Greengenes databases that allowed taxonomic classification of bacterial sequences to OTUs. The results obtained from both databases differed considerably in the number of OTUs, and only the Greengenes database allowed identification of Wolbachia (infection was also supported by comparison of sequences to NCBI database). The putative bacterial endosymbiont Wolbachia was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…The life cycle of tardigrades poses a unique selective pressure on any permanent residents of the microbiota, as these organisms would also have to survive within the tardigrade during cryptobiosis. This would be especially true for the obligate endosymbiotic taxa Rickettsiales and Polynucleobacter previously observed in tardigrades (Vecchi et al 2018;Roberto Guidetti et al 2020;Kaczmarek et al 2020;Mioduchowska et al 2021), as well as for the Rickettsia identified in the current study (see below).…”
Section: Tardigrade Community Microbiome By Contrastsupporting
confidence: 55%
See 4 more Smart Citations
“…The life cycle of tardigrades poses a unique selective pressure on any permanent residents of the microbiota, as these organisms would also have to survive within the tardigrade during cryptobiosis. This would be especially true for the obligate endosymbiotic taxa Rickettsiales and Polynucleobacter previously observed in tardigrades (Vecchi et al 2018;Roberto Guidetti et al 2020;Kaczmarek et al 2020;Mioduchowska et al 2021), as well as for the Rickettsia identified in the current study (see below).…”
Section: Tardigrade Community Microbiome By Contrastsupporting
confidence: 55%
“…In this study, the five most abundant phyla were Proteobacteria, Firmicutes, Bacteroidota, Actinobacteria, and Acidobacteria (Table S10). All of these except Acidobacteria were previously reported as highly abundant in at least two of the three previous tardigrade microbiome surveys that presented results at a phylum level, with Proteobacteria identified as the most abundant phylum in all cases (Vecchi et al 2018;Kaczmarek et al 2020;Mioduchowska et al 2021). Combined, the tardigrades in these studies represent a diverse set of species, including wild and laboratory-reared specimens isolated from multiple continents, suggesting that the predominance of these phyla is broadly characteristic of the microbiome of Tardigrada, regardless of species or location.…”
Section: Tardigrade-associated Taxamentioning
confidence: 86%
See 3 more Smart Citations